KANDUNGAN KLOROFIL DAUN PADA EMPAT JENIS POHON DI ARBORETUM SYLVA INDONESIA PC. UNIVERSITAS TANJUNGPURA - Zakiyah, Miftahul; Manurung, Togar F; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2018)
Photosynthesis is the process of changing inorganic compounds (CO2 and H2O) into organic compounds (carbohydrates) and O2 with the help of sunlight. Chlorophyll is a major factor affecting photosynthesis. Chlorophyll is a green pigment found in most plants, algae, and also cyanobacteria. The aim of this research was to know and compared the difference of chlorophyll content of 4 (four) tree species consisting of Fast Growing Species is Macaranga pruinosa & Acacia mangium and Slow Growing Species is Shorea seminis and Shorea balangeran at the Sylva Arboretum Indonesia PC. Universitas Tanjungpura. This research use Purposive Sampling method. The value of leaf chlorophyll content in each tree species were Macaranga pruinosa 41,63 (chlorophyll / mm2), Acacia mangium 50,21 (chlorophyll / mm2), Shorea seminis 59,09 (chlorophyll / mm2), and Shorea balangeran of 61.58 (chlorophyll / mm2). The average value of chlorophyll content in the fast growing species was 45.92 (chlorophyll / mm2) and in the group of slow growing species was 60.33 (chlorophyll / mm2). The difference of chlorophyll content in the group of Fast Growing Species and Slow Growing Species give a significant at 5% significance level to chlorophyll content. The chlorophyll value of the Fast Growing Species has a smaller chlorophyll content of 45.92 (chlorophyll / mm2) compared to the chlorophyll value of Slow Growing Species that was equal to 60,33 (chlorophyll / mm2). Difference in chlorophyll content in both groups are influenced by environmental factors such as light intensity, temperature and humidity.Keywords: Chlorophyll, Fast Growing Species, Slow Growing Species